Towards the reconstruction of planning theory - Dabović Tijana; Đorđević Dejan (Glasnik Srpskog Geografskog Društva, 2008)
This article intends to determine whether or not the extensive debate within the Planning Theory has led to a better understanding of the meaning 'planning' and a clarification of its role. Since the response to this question is negative, the article will examine: what are the reasons for that situation and under what conditions a further development of the debate and research can achieve a real contribution to what should be its main objectives - better understanding of planning and helping to perfect its methods.